Holocene vegetation and flora dynamics of the west Cork/Kerry region, south-western Ireland - Michael O’Connell; Anette Overland (Vegetation History and Archaeobotany, 2025)
Sediments from a small lake, Loch Beag, in Barrees, Beara peninsula, south-western Ireland, provide a record of vegetation history that spans most of the Lateglacial and Holocene (14–0.43 ka). The detailed part of the record relates to the Holocene, which is the focus of this paper. The investigations carried out include pollen and macrofossil analyses, loss-on-ignition measurements and 14 C dating. As well as providing records for tree and shrub taxa, and especially Pinus , Quercus , Ulmus , Fraxinus and Taxus , other taxa mainly with Atlantic and/or Lusitanian distributions are also considered. These include Arbutus unedo (strawberry tree) and fern species such as Osmunda regalis, and the filmy ferns Hymenophyllum tunbrigense , H. wilsonii and Trichomanes speciosum (Killarney fern). Detailed records for a suite of bog/heath taxa, including ericoid species ( Erica tetralix and E. cinerea ), Narthecium ossifragum , Hypericum elodes and Myrica gale , are presented. The results of 14 C dating of bog-pines from western Ireland are summarised. Results of other investigations, including key Holocene pollen diagrams, and charcoal and fossil-wood records from archaeological excavations that relate mainly to the Bronze Age in the wider west Cork/Kerry region, are reviewed. Vegetation dynamics, human impact and plant biogeography are discussed in the light of the considerable data now available for the region.